2019
DOI: 10.1017/s1352465819000274
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing core beliefs in psychosis: a qualitative study

Abstract: Background: Cognitive behavioural treatments are recommended for people with psychosis. Core beliefs regarding the self and others are a key part of the models underpinning cognitive behavioural therapy but detailed understanding of these putative beliefs in people with psychosis are limited. A greater understanding of these mechanisms is necessary to improve and refine treatments.Aims: This study utilized a qualitative approach to explore core schematic beliefs in psychosis (strongly held positive and negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In the remaining 18 studies (325 participants), classification system criteria were not used consistently, limiting our ability to reliably discriminate participants based on diagnosis. Of these 18 studies, two 58,60 confirmed diagnosis through a diagnostic interview based on ICD or DSM criteria, one 49 confirmed diagnosis through consensus, and 15 5,18,37,39,[45][46][47][48]51,53,54,56,57,59,62 current or past experience of delusions were included in nine studies, 18,35,46,48,51,54,58,59,61 one study 34 specified that psychotic symptoms were recent, and the remaining eight studies 5,37,41,43,45,47,60,62 did not provide information on timing. Two remaining studies specified that delusions were past 39,57 (table).…”
Section: Resultsmentioning
confidence: 99%
“…In the remaining 18 studies (325 participants), classification system criteria were not used consistently, limiting our ability to reliably discriminate participants based on diagnosis. Of these 18 studies, two 58,60 confirmed diagnosis through a diagnostic interview based on ICD or DSM criteria, one 49 confirmed diagnosis through consensus, and 15 5,18,37,39,[45][46][47][48]51,53,54,56,57,59,62 current or past experience of delusions were included in nine studies, 18,35,46,48,51,54,58,59,61 one study 34 specified that psychotic symptoms were recent, and the remaining eight studies 5,37,41,43,45,47,60,62 did not provide information on timing. Two remaining studies specified that delusions were past 39,57 (table).…”
Section: Resultsmentioning
confidence: 99%
“…The links between schemas and images highlighted in the earlier qualitative study (Taylor et al, 2020) suggest that targeting both schemas and images may reduce distress in psychosis. Imagery can also have a more powerful effect on emotion than verbal language (Holmes and Mathews, 2010), and so has the potential to achieve more powerful change (compared with standard cognitive or thought-based approaches) if used within therapy for people with psychosis.…”
Section: Introductionmentioning
confidence: 92%
“…The intervention was developed by the authors from a number of sources, including a systematic review of schema therapy across mental health disorders , a qualitative study of core beliefs in psychosis (Taylor et al, 2020) and a daily experience sampling method study of positive and negative core schema in psychosis (Taylor et al, manuscript under review). The approach was also influenced by existing cognitive behavioural imagery work (Hackman et al, 2011), an adapted formulation model (Hales et al (2014) and some schema therapy techniques (Young et al, 2003;Arntz and Jacob, 2012); and the researchers' theoretical knowledge and clinical experience.…”
Section: Imaps Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study with small samples of individuals from India, Ghana, and the United States found that while the Indians perceived their AVH as the voices of elders telling them to do simple things and the Ghanaians perceived their AVH as the voice of God, the Americans heard unidentifiable voices which discussed and called for violence (Luhrmann et al, 2015 ). Meanwhile, people with low self-esteem and feelings of being unsafe may hear voices which remind them of experiences of being unsafe (Taylor et al, 2020 ), and may also perceive new people as threatening on the basis of little evidence (Garrett et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%